Listening to the Song of the Wind: The Mediating Role of Sigur Rós on Chinese Audiences’ Perceptions of Iceland - Zhenwen Lai 1996- (2023)
This qualitative study examines the perceptions of Chinese individuals towards Iceland and the role of Sigur Rós’ music in shaping those perceptions. Utilizing thematic analysis on comments and reviews of Heima and Ágætis byrjun on Douban, the study identifies recurring themes related to the natural and social aspects of Iceland. Additionally, the study delves into the sociological factors contributing to Chinese audiences’ imaginaries of Iceland, particularly in contrast to the high-stress and competitive social landscape of China. The study’s findings suggest that Sigur Rós’ fanciful and romanticized portrayals of Iceland as an otherworldly space, coupled with the otherness of their music, contribute to an idyllic and utopian image of Iceland in the minds of Chinese audiences. The study’s contribution to the field lies in its presentation of Chinese audiences’ perceptions of Icelandic popular music, filling a research gap in the existing literature. Furthermore, the study emphasizes the need for further research to examine the influences of other Icelandic musicians’ works on individuals’ perceptions of Iceland in different contexts. Overall, this study sheds light on the ways in which music can shape individuals’ perceptions of other cultures and highlights the importance of understanding the sociological factors that contribute to these imaginaries.